MRI tractographic validation of drug-enhanced hepatic clearance of amyloid-beta and the therapeutic potential for Alzheimer's Disease: A pilot study - Bhattacharjee A.; Roy P.K. (My University, 2025)
Alzheimer's disease (AD) may require alternative therapeutic perspectives as current interventions may sometimes be sub-optimal. Amyloid-beta 42 (Aβ42) is mainly eliminated by hepatic clearance which diminishes in AD, hence hepatomodulatory drugs enhancing this clearance may have potentiality for therapeutic implication. Here, we clinically substantiate our systems-biology investigation on repurposed hepatomodulating drugs (metformin, cilostazol and rifampicin) which enhance brain insoluble Aβ42 clearance through liver-bile-faeces route. Through MRI-tractographic analysis, we now formulate a three-segmental basis of brain Aβ42 spread: fronto-thalamic region (segment-1), temporo-occipital region (segment-2), and dorso-cingulate region (segment-3). This segmental pattern is corroborated histopathologically by Braak's stages A, B and C. We further observed that the aforesaid three pharmaceuticals respectively acted on those three segmental regions differentially. We analysed MRI and DTI images of 15 healthy controls (CDR: 0; MMSE: 24–20), and 15 AD patients (CDR: 0.5–1.0; MMSE: 20–26). We found that, tractographically, there is a significant reduction in neuronal integrity in the three aforesaid regions in untreated AD compared to controls. Nevertheless, the three drugs increased neural activation of AD patients in the three corresponding areas. These three drugs act by regulating respectively the genes ABCB11, ABCA1 and MDR1. These genes were correspondingly downregulated in the above-mentioned anatomical segments 1, 2 and 3 of Alzheimer's disease. Thus personalized patient-specific hepatomodulative drugs for AD intervention may be explored, as corroborated by the neuroanatomical involvement in AD. © 2023 The Author(s)